HfO2:Y2O3 ultrathin nanolaminate structures grown by ALD: Bilayer thickness and annealing temperature effects on optical properties. Issue 12 (15th June 2022) - López - Medina, J.; Vazquez – Arce, J.; Pizá-Ruiz, P.; Nedev, N.; Farías, M.H.; Tiznado, H.
Abstract: –Ultrathin nanolaminate structures were prepared by sequential HfO2 :Y2 O3 ( HY ) bilayer deposition at 250 °C on n-type (100) silicon wafers via thermal atomic layer deposition (ALD) method. Three sets of four samples were prepared, each sample with a total thickness of the nanolaminate of 54.5 ± 0.8 nm. The nominal thicknesses of the HY bilayers of the four samples were 0.5:0.5 nm, 1:1 nm, 2:2 nm, and 5:5 nm After the deposition, two of the sets were annealed in N2 atmosphere for 1 h at 500 °C and 750 °C, respectively. The third set was used as control samples. The optical behavior of the ultrathin nanolaminate structures was studied as a function of the HY bilayer thickness and annealing temperature. The thickness and optical parameters were analyzed via spectroscopic ellipsometry to gain information about the optical constants and bandgap values. An increase of the refractive index was found when the HY bilayer thickness decreased from 5:5 nm to 0.5:0.5 nm for both annealing temperatures as well as for the as-deposited sample, while the optical bandgap varied between 3.8 eV and 4.5 eV. The obtained results demonstrate the viability of HY ultrathin nanolaminate structures as a dielectric material for application in electronic and/or optoelectronic devices. Furthermore, the optical properties dependence on the bilayer thickness and annealing temperature could offer the possibility to design, fabricate, and improve samples with tunable optical properties at the nanoscale.